Development of Indirect Competitive Immuno-Assay Method Using SPR Detection for Rapid and Highly Sensitive Measurement of Salivary Cortisol Levels - Tahara, Yusuke; Huang, Zhe; Kiritoshi, Tetsuro; Onodera, Takeshi; Toko, Kiyoshi (Frontiers in Bioengineering and Biotechnology, 2014)
The monitoring of salivary cortisol as a key biomarker of an individual’s stress response has been increasingly focused on. This paper describes the development of a novel cortisol biosensor based on an indirect competitive method using a surface plasmon resonance (SPR) immunosensor. The surface of a Au chip was modified with PEG6-COOH aromatic dialkanethiol self-assembled monolayers (SAMs) and hydrocortisone 3-(O-carboxymethyl) oxime (hydrocortisone 3-CMO) as a cortisol analogue. A detection limit of 38 ppt range with a measurement range of 10 ppt to 100 ppb was accomplished without the incubation of a mixing solution consisting of standard cortisol and an anti-cortisol antibody, and the response time was 5 min from the sample injection. We experimentally compared our biosensor with a commercialized salivary cortisol enzyme-linked immunosorbent assay (ELISA) kit using human saliva samples. It was found that the results obtained by the cortisol biosensor had a high correlation with those obtained by ELISA assay (R = 0.96). Our findings indicate the potential utility of the cortisol biosensor for on-site diagnosis and bedside point-of-care testing (POCT) from bedside testing.